The Role of Technology in The Development of Children's Religious Psychology in Madrasah Ibtidaiyah - Prihatiningsih, Dwi Sis; Listyowati; Abidin, Zaenal (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
The development of children's religious psychology in the digital era should be optimized through adaptive technology integration based on religious values, considering that technology offers interactive and interesting media for religious learning. However, the reality in Madrasah Ibtidaiyah shows that the use of technology is still limited, not systematically directed, and tends to be additional without a deep psychological approach. This condition creates a gap between the potential of technology in supporting children's religious development and its less than optimal implementation, including a lack of understanding of the positive impacts and negative risks of using digital media. This study focuses on analyzing the role of technology in the development of children's religious psychology and identifying its impacts in Madrasah Ibtidaiyah. The method used is qualitative literature research with thematic analysis of related digital literature and documentation. The results of the study reveal that technology, especially Islamic applications and interactive media, can strengthen children's religious understanding through a fun approach, but also has the potential to cause distraction or reduction of religious meaning if not managed with the right pedagogical principles. The discussion emphasizes the importance of teacher and parent assistance in filtering content and integrating religious values contextually. The conclusion of the study states that technology plays a significant role in children's religious psychology, but a holistic development framework is needed so that its use is in line with the goals of religious education.